International survey on willingness-to-pay (WTP) for one additional QALY gained: what is the threshold of cost effectiveness? - Shiroiwa, Takeru; Sung, Yoon-Kyoung; Fukuda, Takashi; Lang, Hui-Chu; Bae, Sang-Cheol; Tsutani, Kiichiro (Health economics, 2010)
Although the threshold of cost effectiveness of medical interventions is thought to be £20 000–£30 000 in the UK, and $50 000–$100 000 in the US, it is well known that these values are unjustified, due to lack of explicit scientific evidence. We measured willingness‐to‐pay (WTP) for one additional quality‐adjusted life‐year gained to determine the threshold of the incremental cost‐effectiveness ratio. Our study used the Internet to compare WTP for the additional year of survival in a perfect status of health in Japan, the Republic of Korea (ROK), Taiwan, Australia, the UK, and the US. The research utilized a double‐bound dichotomous choice, and analysis by the nonparametric Turnbull method. WTP values were JPY 5 million (Japan), KWN 68 million (ROK), NT$ 2.1 million (Taiwan), £23 000 (UK), AU$ 64 000 (Australia), and US$ 62 000 (US). The discount rates of outcome were estimated at 6.8% (Japan), 3.7% (ROK), 1.6% (Taiwan), 2.8% (UK), 1.9% (Australia), and 3.2% (US). Based on the current study, we suggest new classification of cost‐effectiveness plane and methodology for decision making. Copyright © 2009 John Wiley & Sons, Ltd.